0009-0002-8145-4997 DEVELOPMENT OF BOUNDARY CONDITIONS FOR MATHEMATICAL MODELS OF UNSTEADY WATER MOVEMENT IN WATER MANAGEMENT FACILITIES - Umarov, Bahrom (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article analyzes the problems of developing boundary conditions for mathematical models taking into account the multidimensional distribution of parameters of unstable water movement in space in modern conditions. The author revealed and explained the solution of the system of equations with boundary conditions for modeling two-dimensional water flow in open channels.